The Effectiveness Of The Flipped Classroom Model On Students’ Activeness And Learning Independence - Alfahral, Reza; Herwin, Herwin; Waruwu, Jefnita Sain (Jurnal Locus Penelitian dan Pengabdian, 2025)
This study investigated the impact of the Flipped Classroom model on student activeness and learning independence in the Primary School Teacher Education (PGSD) Program at Universitas Muhammadiyah Buton. A quasi-experimental method with a nonequivalent control group design was employed. The sample included 30 students in the experimental group who received instruction via the Flipped Classroom model and 29 students in the control group who were taught using the expository method. The research instrument was a questionnaire measuring student activeness and independence, consisting of 18 valid items (r = 0.552–0.957; Sig. < 0.05) and demonstrating high reliability (Cronbach’s Alpha = 0.993). The results showed that both experimental and control groups experienced significant improvements in activeness and independence following the intervention, as evidenced by the Paired Samples T-Test (Sig. = 0.000 < 0.05). However, when comparing the two groups using the Independent Samples T-Test, a significant difference was found in learning independence (Sig. = 0.047 < 0.05), whereas the difference in activeness was not statistically significant (Sig. = 0.574 > 0.05). This suggests that the Flipped Classroom model is more effective in enhancing student independence compared to the expository model, although its effect on activeness did not differ significantly. Consequently, the Flipped Classroom can be regarded as a viable alternative teaching strategy in higher education, particularly for PGSD students, as it promotes greater learning independence while supporting active participation in the learning process.